Ustvarjalnice v splošnih knjižnicah - Švab, Špela (Knjižnica, 2021)
Makerspace is a place where library users can try out and use equipment, devices and tools for various purposes free of charge. This service has become very common in public libraries around the world in the last decade, while in Slovenia there are currently only two public libraries that have experience in developing makerspaces. The paper provides an overview of the development of makerspaces, their purpose and position in public libraries. It also presents some examples of successful makerspaces in public libraries. Special attention is given to service planning of makerspaces and the elements that are critical to their successful operation. Three groups of stakeholders involved in makerspace planning are presented – users, local community, staff and volunteers. Along with recommendations for physical space and equipment in makerspaces, we present a list of equipment with appropriate devices, tools and materials that covers the most common activities in makerspaces. This is the first paper on makerspaces in Slovenia that comprehensively addresses this service in public libraries. It can serve as a starting point for reflection both before the decision to set up a makerspace and in the process of planning.
Keywords: knjižnične storitve; načrtovanje; splošne knjižnice; ustvarjalnice